Effects of neonatal handling on playfulness by means of reversal of the desire to play in rats (Rattus Norvegicus) - Aguilar-Heras, Raúl; Caramés-Tejedor, José María; Espinet-Rubio, Alfredo (American Psychological Association, 2009)
In the present study the authors sought to establish whether the range of effects of neonatal handling stimulation (H), that is, brief daily periods of infant isolation, could be extended to the domain of social motivation. With this aim, the authors studied the innate motivation to engage in rough-and-tumble play (R&T) in adolescent rats (Rattus norvegicus) by means of a reversal design, in which half of the rats were first housed in isolation (Days 1–3), and then in company (Days 4–6), while the other half followed the reverse sequence of housing conditions. Results showed in a clear-cut manner that H fuelled playfulness, as measured by pin and dorsal contact episodes, with (relative) independence of trait-based differences in fearful behavior between handled and nonhandled rats. Given that the different levels of the rat’s social brain are apparently sensitive to tactile stimulation in infancy, the authors propose that the vibrant R&T reported here could reflect an enduring alteration of genetically based, motivational systems underlying playfulness and, perhaps, positive social emotions like joy.
Keywords: Animales - Conducta social; social behavior; play motivation; emotion; neonatal handling; Wistar rats